Electronic Structure of the Ferryl Intermediate in the α-Ketoglutarate Dependent Non-Heme Iron Halogenase SyrB2: Contributions to H Atom Abstraction Reactivity - Srnec, Martin; Wong, Shaun D; Matthews, Megan L; Krebs, Carsten; Bollinger, J Martin; Solomon, Edward I (Journal of the American Chemical Society, 2016)
Low temperature magnetic circular dichroism (LT MCD) spectroscopy in combination with quantum-chemical calculations are used to define the electronic structure associated with the geometric structure of the Fe(IV)═O intermediate in SyrB2 that was previously determined by nuclear resonance vibrational spectroscopy. These studies elucidate key frontier molecular orbitals (FMOs) and their contribution to H atom abstraction reactivity. The VT MCD spectra of the enzymatic S = 2 Fe(IV)═O intermediate with Br(-) ligation contain information-rich features that largely parallel the corresponding spectra of the S = 2 model complex (TMG3tren)Fe(IV)═O (Srnec, M.; Wong, S. D.; England, J; Que, L; Solomon, E. I. Proc. Natl. Acad. Sci. USA 2012, 109, 14326-14331). However, quantitative differences are observed that correlate with π-anisotropy and oxo donor strength that perturb FMOs and affect reactivity. Due to π-anisotropy, the Fe(IV)═O active site exhibits enhanced reactivity in the direction of the substrate cavity that proceeds through a π-channel that is controlled by perpendicular orientation of the substrate C-H bond relative to the halide-Fe(IV)═O plane. Also, the increased intrinsic reactivity of the SyrB2 intermediate relative to the ferryl model complex is correlated to a higher oxyl character of the Fe(IV)═O at the transition states resulting from the weaker ligand field of the halogenase.
Keywords: Glutarates; Models, Molecular; cirkulární dichroismus; Quantum Theory; Iron Compounds; kvantová teorie; nehemové proteiny obsahující železo; Hydrogen; Threonine; vodík; Bacterial Proteins; threonin; molekulární modely; Nonheme Iron Proteins; Circular Dichroism; Oxidoreductases; sloučeniny železa; glutaráty; bakteriální proteiny; oxidoreduktasy